Respuesta :

Answer:

Solving the expression  [tex]\frac{\sqrt[3]{7} }{\sqrt[5]{7} }[/tex] we get [tex]\mathbf{7^{\frac{2}{15}}}[/tex]

Option D is correct option.

Step-by-step explanation:

We need to solve the expression: [tex]\frac{\sqrt[3]{7} }{\sqrt[5]{7} }[/tex]

We know that

[tex]\sqrt[3]{x}=x^{\frac{1}{3}[/tex] and [tex]\sqrt[5]{x}=x^{\frac{1}{5}[/tex]

Using above rule:

[tex]\frac{\sqrt[3]{7} }{\sqrt[5]{7} }\\=\frac{7^{\frac{1}{3}}}{7^{\frac{1}{5}}}[/tex]

Now, we know the exponent rule if bases are same and divided then exponents are subtracted i.e:  [tex]\frac{a^m}{a^n}=a^{m-n}[/tex]

Using the exponent rule

[tex]=7^{\frac{1}{3}-\frac{1}{5} }\\Simplifying\:exponents\\=7^{\frac{5-3}{15}}\\=7^{\frac{1*5-1*3}{15}}\\=7^{\frac{2}{15}}[/tex]

So, solving the expression  [tex]\frac{\sqrt[3]{7} }{\sqrt[5]{7} }[/tex] we get [tex]\mathbf{7^{\frac{2}{15}}}[/tex]

Option D is correct option.

ACCESS MORE